Preferences for Attention-Deficit/Hyperactivity Disorder (ADHD) Non-Stimulant Treatment Characteristics Among Children and Adolescents With ADHD and Their Caregivers - Emuella Flood; Kavita Gajria; Vanja Sikirica; Paul Hodgkins; M. Haim Erder; Frank Lopez; Daniel Connor (Journal of Health Economics and Outcomes Research)
# Background Understanding patient and caregiver preferences for treatment is important for optimizing treatment decisions. Non-stimulant therapies are an alternative treatment option to stimulant therapy for attention-deficit/hyperactivity disorder (ADHD). Guanfacine extended release (GXR) and atomoxetine (ATX) are two non-stimulant medications approved in the United States for the treatment of ADHD.